Finite mathematics - Rolf, Howard Leroy (Thomson Brooks/Cole, 2008)
Get the background you need for future courses and discover the usefulness of mathematical concepts in analyzing and solving problems with FINITE MATHEMATICS, 7th Edition. The author clearly explains concepts, and the computations demonstrate enough detail to allow you to follow-and learn-steps in the problem-solving process. Hundreds of examples, many based on real-world data, illustrate the practical applications of mathematics. The textbook also includes technology guidelines to help you successfully use graphing calculators and Microsoft Excel to solve selected exercises.